Peran Layanan Konseling Individual terhadap Pemulihan Psikologis Remaja yang Mengalami Trauma Emosional akibat Ketidakharmonisan Keluarga - Inez Echa Aurel Nasution; Anni Mardia Sagala; M. Farhan; Ainul Mardiyah (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
This study aims to describe the implementation and effectiveness of individual counseling services in helping the psychological recovery of adolescents who have experienced emotional trauma due to family disharmony. Using a qualitative case study method on three adolescents with different traumatic backgrounds—parental conflict, verbal abuse, and broken homes this study examines their psychological conditions before and after receiving counseling. The results show that individual counseling was carried out through rapport building, exploration of the source of trauma, and the use of intervention techniques such as cognitive behavior therapy, mindfulness, and expressive methods. After undergoing counseling, the three clients showed positive changes in the form of decreased anxiety, increased self-esteem, improved ability to express emotions, and improved social relationships. Factors supporting the effectiveness of counseling included a good therapeutic relationship, consistency of sessions, and flexibility of methods, while obstacles included a lack of family support and emotional instability in adolescents. Overall, individual counseling proved effective in facilitating the psychological recovery of adolescents experiencing emotional trauma.